Brill's companion to Greek and Latin pastoral - Fantuzzi, Marco.; Papanghelis, Theodore D. (Brill's Companions to Classical Studies., 2006)
This volume comprises articles by an international team of twenty-three scholars. The contributions focus on the historical genesis, stylistic and narrative features and evolution of pastoral, both as genre and mode, from Theocritus to the Byzantine period. Special attention has been paid to the idea of the 'invention of a fictionalized tradition', and to pastoral's thematic and formal relationship with other literary genres. In their totality, the contributions, as well as offering a comprehensive overview of the more or less familiar issues and ideas discussed in connection with pastoral, point to new emphases, trends and insights in current scholarly work in this area. The volume is addressed to a wide range of students and scholars in classics, but much in it will also be of interest to those working in the fields of comparative and modern literatures.